Structure-Dependent Modulation of Aryl Hydrocarbon Receptor-Mediated Activities by Flavonoids. (23rd March 2018) - Jin, Un-Ho; Park, Hyejin; Li, Xi; Davidson, Laurie A; Allred, Clinton; Patil, Bhimanagouda; Jayaprakasha, Guddadarangavva; Orr, Asuka A; Mao, Leevin; Chapkin, Robert S; Jayaraman, Arul; Tamamis, Phanourios; et al.
Abstract: Dietary flavonoids are used in treatment of multiple diseases, and their antiinflammatory effects in the intestine are due, in part, to interactions with gut microflora and possibly due to modulation of aryl hydrocarbon receptor (AhR) signaling. In this study, we investigated the structure-dependent AhR activity of 14 flavonoids in Caco2 colon cancer cells using induction of CYP1A1 and UGT1A1 gene expression as endpoints. A major structural determinant for AhR activation was the number of hydroxyl groups where pentahydroxyflavonoids (with the exception of morin) > hexahydroxyflavonoids > tetra-/trihydroxyflavonoids, and some of the latter compounds such as apigenin exhibited AhR antagonist activity for induction of CYP1A1. Simulations suggest that while quercetin and apigenin interact primarily with the same residues, the strength of interactions between specific AhR residues with CYP1A1 agonist, quercetin, in comparison with CYP1A1 antagonist, apigenin, is different; thus, such interactions are presumably indicative of potential switches for modulating CYP1A1 activity. The structure-dependent effects of the hydroxyl flavonoids on induction of UGT1A1 were similar to that observed for induction of CYP1A1 except that luteolin and apigenin induced UGT1A1 levels similar to that observed for TCDD, whereas both compounds were AhR antagonists for CYP1A1. Thus, the effects of the flavonoids in Caco2 cells on Ah-responsiveness and interactions with butyrate were both ligand structure- and response-dependent and these activities are consistent with hydroxyflavonoids being selective AhR modulators.